Effect of Competence, Workload, Leadership on Nurse Performance - Memed Sena Setiawan; Septirina Rahayu (JOURNAL EDUCATIONAL OF NURSING(JEN), 2020)
The purpose of this study was to obtain an empirical description of the influence of competence, workload, leadership on nurse performance jointly or partially. Sampling using the Probability Sampling technique, which is a technique of giving equal opportunities to all members of the population selected to be the sample. The sample in this study was 50. The research method used in this research is descriptive qualitative method and the data analysis method used is multiple regression. Based on the research results, it can be concluded that competence has a significant effect on nurse performance as indicated by a significance value